PENDAMPINGAN KETERLIBATAN MASYARAKAT DALAM PENDATAAN PENDARATAN GURITA UNTUK MENDUKUNG PENGELOLAAN SUMBER DAYA IKAN BERKELANJUTAN DI SELAT ALAS - Muslihuddin Aini; Iqlima Putri; Dinda Kharisma Hafizah; Soraya Gigentika; Ayu Adhita Damayanti; M. Junaidi (Universitas Mataram, 2025)
The Alas Strait is a marine area with abundant potential of octopus (Octopus cyanea), serving as a primary livelihood source for coastal communities in Seruni Mumbul and Seriwe Villages, East Lombok Regency. However, the lack of catch landing data has become a major challenge in achieving sustainable fisheries management. This activity aimed to enhance community capacity and participation in recording octopus landing data through a participatory approach. The method consisted of two main stages: socialization and technical training. The results showed an improvement in community understanding of the importance of fisheries data, as well as their ability to routinely record catch information, including the number, size, location, and time of landings. In addition, local collectors were involved as they have direct access to fishers’ catches. The data collected are valuable as a basis for management policies, such as the establishment of conservation zones and seasonal closures. This activity strengthened the role of the community as an essential part of the fisheries resource management system. The findings suggest that community involvement in octopus landing data collection directly supports the development of a participatory, adaptive, and sustainable management system.